Studi Kontribusi Perceived Organizational Support terhadap Employee Well-Being - Alfiyyah Fitri Ramadhani; Ali Mubarak (Jurnal Riset Psikologi, 2023)
Abstract. Perceived organizational support is the employee's perception of the extent to which the organization values contributions and cares about their well-being. Employee well-being is employee welfare consisting of subjective well-being, workplace well-being, and psychological well-being. This research aims to find out the description and contribution of perceived organizational support to employee well-being in lecturers at religion-based tertiary institutions in the city of Bandung. This study uses a quantitative method with multiple regression analysis. The measurement tool used to measure perceived organizational support variables is a survey of perceived organizational support developed by Eisenberger et al (1986). To measure employee well-being variables using the employee well-being scale developed by Zheng et al (2015). The results of this study indicate that 89.6% of lecturers have high perceived organizational support and 98.9% of lecturers have high employee well-being. This study shows the results that perceived organizational support affects employee well-being by 27.4%. Partially, the dimensions of evaluative judgment attributes to the organization on perceived organizational support have a positive and significant effect on employee well-being, while the dimensions of actions affecting the perceived organizational support do not have a significant effect on employee well-being. Abstrak. Perceived organizational support merupakan persepsi karyawan mengenai sejauh mana organisasi dapat menghargai kontribusi dan peduli mengenai kesejahteraan mereka. Employee well-being merupakan kesejahteraan yang dimiliki karyawan yang terdiri dari subjective well-being, workplace well-being, dan psychological well-being. Tujuan dari penelitian adalah untuk mengetahui gambaran dan kontribusi perceived organizational support terhadap employee well-being pada dosen perguruan tinggi berbasis agama di Kota Bandung. Penelitian ini menggunakan metode kuantitatif dengan analisis regresi berganda. Alat ukur yang digunakan dalam mengukur variabel perceived organizational support adalah survey of perceived organizational support yang dikembangkan oleh Eisenberger et al (1986), untuk mengukur variabel employee well-being menggunakan employee well-being scale yang dikembangkan oleh Zheng et al (2015). Hasil penelitian ini menunjukkan bahwa sebesar 89,6% dosen memiliki perceived organizational support yang tinggi dan 98,9% dosen memiliki employee well-being yang tinggi. Penelitian ini menunjukkan hasil bahwa perceived organizational support berpengaruh terhadap employee well-being sebesar 27,4%. Secara parsial, dimensi evaluative judgement attributes to the organization pada perceived organizational support memiliki pengaruh positif dan signifikan terhadap employee well-being, sedangkan dimensi actions affecting the pada perceived organizational support tidak memiliki pengaruh yang signifikan terhadap employee well-being.